The Relationship between Spiritual Intelligence and Emotional Intelligence with Performance of Female Nurses in Tabriz Hospitals in 2018 - Shahram Ranjdoust (Shahid Beheshti University of Medical Sciences, 2020)
For downloading the full-text of this article please click here. Background and Objective: The most important goal of any organization is to achieve the highest level of optimal efficiency. One of the most important factors involved in optimal efficiency is the human resources. Nurses, as one of the most important human resources in hospitals, are affected by several factors including emotional intelligence and spiritual intelligence, which can lead to quality improvement in health services and productivity. The aim of this study was to investigate the relationship of spiritual intelligence and emotional intelligence with job performance of nurses in hospitals of Tabriz. Methods: This study was applied in terms of purpose and descriptive-correlational in terms of method. The sample population of this study included all the female nurses in Tabriz out of which 360 were selected using Morgan table and multi-stage cluster random sampling method. Data was collected using questionnaires including emotional intelligence (Siberia Shearing), spiritual intelligence (king), job performance (Paterson) questionnaires. The collected data was analyzed using Pierson Correlation Coefficient and regression. In this study, all the ethical considerations have been observed and no conflict of interest was reported by the author. Results: The results showed that there was a meaningful relationship between the components of spiritual intelligence and emotional intelligence and the performance of female nurses (P>0.05). There was also a significant relationship between the components of emotional intelligence and spiritual intelligence components of nurses (P<0.05). Based on the regression results, emotional intelligence predicted 19/18 percent of the variance in spiritual intelligence (P<0.05). Emotional intelligence predicted 5/8 percent (P<0.05) and the spiritual intelligence predicted 1/2 percent of the variance in performance (P<0.05). Conclusion: Based on the results of the study, it can concluded that nurses' performance can be enhanced through Spiritual Intelligence and Emotional Intelligence. Having emotional and spiritual intelligence skills can help to improve nursing performance and the equality of services among patients. Hence, hospital managers should take the required measures for promoting the emotional and spiritual intelligence of nurses. For downloading the full-text of this article please click here. Please cite this article as: Ranjdoust Sh. The Relationship between Spiritual Intelligence and Emotional Intelligence with Performance of Female Nurses in Tabriz Hospitals in 2018. Journal of Pizhūhish dar dīn va salāmat. 2020;6(1):19-35. https://doi.org/10.22037/jrrh.v6i1.19852